Geographic Segmentation using Application Programming Interface (API) Geolocation on E-Marketplace Development - Arif Amrulloh; Yudha Saintika (Jurnal CoreIT: Jurnal Hasil Penelitian Ilmu Komputer dan Teknologi Informasi, 2023)
Purbalingga is one of the regencies in the province of Central Java with many muffler artisans and is the largest exhaust producer in Indonesia. In this study, the development of an e-marketplace application will be carried out by implementing a geolocation Application Programming Interface (API). The geolocation API is used to detect the location of visitors so that price differences can be made based on the visitor's country. The system development method used is Rapid Application Development (RAD). The RAD method is used because application development can be done in a relatively fast time. At the system design stage, the Unified Modeling Language (UML) is used as a visual model to facilitate the application development. The final result of this research is an e-marketplace application that specifically sells exhaust products and accessories. The test results were carried out in 6 different locations with details of 4 countries of Indonesia, one country of Malaysia, and one country of Saudi Arabia. Other prices were obtained according to the location of the visitor's country.